Recent Development of Graphene Based Electrochemical Sensor for Detecting Hematological Malignancies-Associated Biomarkers: A Mini-Review - Wei, Shougang; Chen, Xiuju; Zhang, Xinyu; Chen, Lei (Frontiers in Chemistry, 2021)
Hematologic malignancies are a group of malignant diseases of the hematologic system that seriously endanger human health, mainly involving bone marrow, blood and lymphatic tissues. However, among the available treatments for malignant hematologic diseases, low detection rates and high recurrence rates are major problems in the treatment process. The quantitative detection of hematologic malignancies-related biomarkers is the key to refine the pathological typing of the disease to implement targeted therapy and thus improve the prognosis. In recent years, bioelectrochemical methods for tumor cell and blood detection have attracted the attention of an increasing number of scientists. The development of biosensor technology, nanotechnology, probe technology, and lab-on-a-chip technology has greatly facilitated the development of bioelectrochemical studies of cells, especially for blood and cell-based assays and drug resistance differentiation. To improve the sensitivity of detection, graphene is often used in the design of electrochemical sensors. This mini-review provides an overview of the types of hematological malignancies-associated biomarkers and their detection based on graphene assisted electrochemical sensors.